9.2k views
3 votes
Find the solution to the system of equation -2x+2y=-4 3x+3y=-18

User Cxreg
by
5.5k points

1 Answer

4 votes

Answer:

(x, y) = (-2, -4)

Explanation:

I like to start by putting the equations into standard form. That requires removing any common factors and making the leading coefficient positive.

-2x +2y = -4 ⇒ x -y = 2 . . . . . . divide by -2

3x +3y = -18 ⇒ x +y = -6 . . . . . divide by 3

__

Now, we can add these two equations to eliminate y:

(x -y) +(x +y) = (2) +(-6)

2x = -4 . . . . simplify

x = -2 . . . . . divide by 2

Substituting into the second equation gives ...

-2 +y = -6

y = -4 . . . . . add 2

The solution to the system of equations is (x, y) = (-2, -4).

Find the solution to the system of equation -2x+2y=-4 3x+3y=-18-example-1
User Lbottoni
by
5.3k points